Evaluating silver-plated nylon (Ag/PA66) e-textiles for bioelectrical impedance analysis (BIA) application. (13th April 2020) - Logothetis, Irini; Vatansever Bayramol, Derman; Gil, Ignacio; Dabnichki, Peter; Pirogova, Elena
Abstract: Bioelectrical impedance analysis (BIA) is an established method for assessing integrity of biotissue. Adapting BIA as a diagnostic tool to monitor electrophysiological activity gives rise to evidence-based objective diagnostic approaches as opposed to visual assessment currently performed by practitioners in wound healing management. Advancements in the telecommunication and textile industries have made the Internet of Wearable Things (IoWT), the future of telemedicine. E-textile electrodes give us the ability for long-term monitoring applications; however, they are associated with electrode polarization impedance ( Zp ) contributing to the electrode-skin impedance ( Zes ). By studying the design of e-textile electrodes, we can reduce Zp and characterise it relative to changes in skin properties, such as skin temperature and perspiration. In this study, we examined the effects of selected textile substrates on changes in Zp of e-textile electrodes, and characterized Zp in a climatic chamber with temperature and relative humidity settings emulating skin temperature and perspiration. An air permeability test was also conducted to account for the physiological comfort of the e-textile electrodes. Our results demonstrate that a polyester non-woven felt substrate is ideal for use in e-textile electrodes. By understanding and quantifying the relationship between Zp, skin temperature and perspiration, this insight can be incorporated into the calibration process of BIA systems for accurate long-term monitoring, resulting in an objective assessment of changes in tissue integrity.